Early Childhood Education in Nigeria; Policy Implementation - Ibrahim, Yakubu Wunti; Igba JI, Clement; Alhaji, Nura; Haruna, Sanusi (Kashere Journal of Education, 2025)
Early childhood education is the first step in a child's overall development and is an important part of the Nigerian education system. It is formally recognised in the National Policy on Education of the Federal Republic of Nigeria (FRN, 2012), which outlines the objectives, standards and implementation guidelines for the effective delivery of pre-primary education across the country. In line with this policy, government efforts are complemented by strong encouragement of private sector participation in the provision and management of early childhood education services. This article critically examines the extent to which the provisions of the National Policy on Education for early childhood education have been implemented in Nigeria. Specifically, the study highlights the core purposes of early childhood education, assesses the achievements recorded since the adoption of the policy, and identifies persistent challenges confronting effective implementation, including issues related to access, quality assurance, funding, infrastructure and teacher preparation. The paper further analyses the implications of these challenges for children’s early learning outcomes and long-term educational development. Based on the findings of the review, practical and policy-orientated recommendations are proposed to strengthen regulatory frameworks, improve professional training for early childhood educators, enhance monitoring mechanisms and promote equitable access to quality early childhood education. The article concludes that sustained government commitment and strategic public–private collaboration are essential for achieving the goals of early childhood education in Nigeria and for ensuring a strong foundation for lifelong learning and national development.